REDUCING DEPRESSION IN PREGNANCY AND POSTPARTUM PERIOD THROUGH ACCEPTANCE AND COMMITMENT THERAPY: A REVIEW OF DEPRESSION REDUCTION AMONG IRANIAN WOMEN - Nastaranalsadat Hosseini; Poh Li Lau; Diana-Lea Baranovich; Norsafatul Aznin A.Razak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Pregnancy is an important event in the life of every woman that is associated with conflicting emotions. Having a newborn baby can be accompanied by hardships and loss of desire, as well as other stresses in life, all of which can have adverse effects on the mental health of the mother and her family. Depression is a common mental disorder in mothers during and after childbirth, which can have negative consequences for mother and baby. Acceptance and Commitment Therapy (ACT) is one of the new treatments with a positive impact on the reduction of depression during pregnancy and afterward. This form of psychotherapy is significant in increasing the psychological flexibilities of women as well as reducing their distress and depressive symptoms during pregnancy and during the postpartum period. Hence this paper aims to review the literature on the concept of depression, its symptoms, and outcomes during pregnancy and the postpartum period, and subsequently, it reviews how ACT can reduce depression, in terms of relevance to Iranian mothers. The studies were selected and identified through online databases from relevant published articles in psychology, psychotherapy, and mental health journals. The reviews of the literature on the ACT and reducing depression in pregnancy and postpartum period were identified from research studies in Iran from 2015 to the present time. This paper highlights the significance of future research into ACT for reducing depression during pregnancy and the postpartum period among Iranian women.